The role of technological capability in the internationalization of the company and new product success: a systematic literature review - Guerra, Rodrigo Marques de Almeida; Camargo, Maria Emília (Internext, 2016)
<span style="font-size: 12.0pt; line-height: 150%; font-family: ’Times New Roman’,serif; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The constant changes in the existing corporate environment require organizations to submit high speed to adapt to hypercompetitive scenarios. Technological capability can promote company internationalization as it enables the formation of strategic partnerships, investment in R&D, resource sharing, technology transfer, and economies of scale. The aim of this article is to conduct a systematic review of the literature on the role of technological capability in company internationalization and new product success (NPS). It was therefore necessary to analyze 87 articles obtained from four databases. The survey results suggest that technological capability can be used as a moderating variable; technological capability is considered an important element of economic growth; it facilitates company internationalization; can provide NPS; technology transfer assists the formation of technological capability through the tacit knowledge, skills, and competencies of staff; as a rule, export companies have greater technological capabilities. Finally, a theoretical framework, study limitations, and suggestions for future research are proposed.